Genome-Wide Association Study for Chronic Hepatitis B Infection in the Thai Population - Ashouri, Saeideh; Khor, Seik-Soon; Hitomi, Yuki; Sawai, Hiromi; Nishida, Nao; Sugiyama, Masaya; Kawai, Yosuke; Posuwan, Nawarat; Tangkijvanich, Pisit; Komolmit, Piyawat; Tsuiji, Makoto; Shotelersuk, Vorasuk; et al. (Frontiers in Genetics, 2022)
To identify novel host genetic variants that predispose to hepatitis B virus (HBV) persistence, we performed the first genome-wide association study in the Thai population involving 318 cases of chronic hepatitis B and 309 healthy controls after quality control measures. We detected the genome-wide significant association of the HLA class II region (HLA-DPA1/DPB1, rs7770370, p-value = 7.71 × 10-10, OR = 0.49) with HBV chronicity. Subsequent HLA allele imputation revealed HLA-DPA1*01:03 (Pc = 1.21 × 10-6, OR = 0.53), HLA-DPB1*02:01 (Pc = 2.17 × 10-3, OR = 0.50), and HLA-DQB1*06:09 (Pc = 2.17 × 10-2 , OR = 0.07) as protective alleles, and HLA-DPA1*02:02 (Pc = 6.32 × 10-5, OR = 1.63), HLA-DPB1*05:01 (Pc = 1.13 × 10-4, OR = 1.72), HLA-DPB1*13:01 (Pc = 4.68 × 10-2, OR = 1.60), and HLA-DQB1*03:03 (Pc = 1.11 × 10-3, OR = 1.84) as risk alleles for HBV persistence. We also detected suggestive associations in the PLSCR1 (rs35766154), PDLIM5 (rs62321986), SGPL1 (rs144998273), and MGST1 (rs1828682) loci. Among single-nucleotide polymorphisms in the PLSCR1 locus, rs1061307 was identified as the primary functional variant by in silico/in vitro functional analysis. In addition to replicating the association of the HLA class II region, we detected novel candidate loci that provide new insights into the pathophysiology of chronic hepatitis B.